METODE DAKWAH PADA KOMUNITAS MARJINAL - Sayuthi Atman Said; Finsa Adhi Pratama (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Globalization flow getting stronger forces each individual to adjust to social life, especially in urban areas. In general, urban communities have begun to classify themselves into communities, both cultural and structural, both small and large communities. One of the communities that was born was a marginal community. This community has a very unique character and orientation and is rarely touched by preaching. Starting from here, this research aims to formulate Islamic preaching method that is suitable for the marginalized communities in Indonesian society. The research method used is qualitative research. In fact, qualitative research does not have a standard measure, the framework that is built can still be reconstructed and adapted to the objective conditions in the field. The approach used is phenomenology. This approach allows researchers to describe experiences as best as possible, understand and apply fairly to phenomena as they appear and are felt by experiences. The conclusion of this research is that the Islamic preaching method that is considered suitable for marginalized communities is da'wah bil hal, study centers, open houses, mentoring and advocacy, economic empowerment, educational scholarships, distribution of Zakat Infaq Sodaqoh (ZIS), library parks, health packages, compensation social and educational skills work.